Assessment of the knowledge and practice on nursing management of Myocardial infarction and Angina among staff nurses with a view to develop informational booklet: A hospital-based study - Mr. Ram Lakhan Mali; Prof. (Dr.) Maharaj Singh (The Bioscan, 2024)
Introduction: Myocardial Infarction (MI) and Angina are the leading cause of morbidity and mortality globally, including India. These conditions require immediate medical attention and continuous management to prevent complications and improve patient outcomes. The role of nurses in the management of MI and Angina is critical, as they are responsible for the initial assessment, monitoring, administration of medications, and educating patients about life style modifications. Despite the central role of nurses in the management of these conditions, there is limited research on the knowledge and practices of nurses involving in care of patient with cardiovascular conditions. Material and Methods: A quantitative research approach with non-experimental descriptive research design was used to conduct the study. Sample size consisted of 100 staff nurses working in selected hospitals of district, Mohali. Convenience sampling technique was used to select study subject. Data collection was performed using a structured knowledge questionnaire to assess the nurses' knowledge of MI and Angina, and structured self-reported checklist to assess nursing practices. The questionnaire was designed based on national and international guidelines for MI and Angina management, and was pre-tested for reliability and validity. Collected data were tabulated and analyzed by using descriptive and inferential statistics. Results: The study result shows that out of 100 staff nurses, majority of staff nurses 68% were having average knowledge, 18% were having good knowledge and 14% were having poor knowledge. Whereas results regarding practices show that majority 59% were having average practice, 29% were having poor practice and 12% were having good levels of practice. A gap between knowledge and practice was evident; despite 70% were having medication knowledge, only 60% implemented it correctly. Nurses who received recent training scored better, highlighting the need for continuous education to enhance practice. Conclusion: The study concluded that majority of staff nurses has a reasonable understanding of the nursing management of MI and Angina. A gap between knowledge and practice was evident. The development and distribution of an informational booklet will serve as a resource for nurses to enhance their knowledge and improve their clinical practices.